Ordinance No. 758, §§ 1-2, Ellensburg City Council (1919) (Ellensburg, Washington). - (:unkn) unknown (General Publisher, 1919)
It shall be unlawful, for any person to manufacture, sell or dispose of, or have in his possession, any instrument or weapon of the kind usually known as slung-shot, sand club, or metal knuckles; or to fertively carry or conceal any dagger, dirk, knife, pistol, or other dangerous weapon; or to use any contrivance or devise for suppressing the noise of any firearm.
--
Keywords: CARRY